MSD2, an apoplastic Mn-SOD, contributes to root skotomorphogenic growth by modulating ROS distribution in Arabidopsis. (April 2022) - Chen, Huize; Lee, Jinsu; Lee, Jung-Min; Han, Minsoo; Emonet, Aurélia; Lee, Jiyoun; Jia, Xingtian; Lee, Yuree
Highlights: MSD2 is an apoplastic manganese superoxide dismutase in Arabidopsis. Peroxynitrite induces Tyr-nitration of MSD2, which inhibits SOD activity. MSD2 expression is highly induced in the roots of etiolated seedlings. MSD2 plays a role in root skotomorphogenesis by regulating ROS distribution. Abstract: Reactive oxygen species (ROS) play essential roles as a second messenger in various physiological processes in plants. Due to their oxidative nature, ROS can also be harmful. Thus, the generation and homeostasis of ROS are tightly controlled by multiple enzymes. Membrane-localized NADPH oxidases are well known to generate ROS during developmental and stress responses, but the metabolic pathways of the superoxide (O2 − ) generated by them in the apoplast are poorly understood, and the identity of the apoplastic superoxide dismutase (SOD) is unknown in Arabidopsis. Here, we show that a putative manganese SOD, MSD2 is secreted and possesses a SOD activity that can be inhibited by nitration at tyrosine 68. The expression of MSD2 in roots is light condition-dependent, suggesting that MSD2 may act on ROS metabolism in roots during the light-to-dark transition. Root architecture is governed by ROS distribution that exhibits opposite gradient of H2 O2 and O2 −, which is indeed altered in etiolated msd2 mutants and accompanied by changes in the onset of differentiation. These results provide a missing link in our understanding of ROS metabolism and suggest that MSD2 plays a role in root skotomorphogenesis by regulating ROS distribution, thereby playing a pivotal role in plant growth and development.